USE OF MATHEMATICS IN BUSINESS PROBLEMS - Sultanov M. M.; Saydaliyeva L. M. (Galaxy International Interdisciplinary Research Journal, 2022)
Theoretical information studied in the school mathematics course is carried out by forming students’ solid mathematical knowledge and skills as a result of applying mathematical concepts, axioms, theorems and mathematical conclusions, laws and rules to a specific problem or task. These questions form the logical thinking of students. It is aimed at developing the skills of proper use of students in the process of solving a problem or examples using methods from the methodology of teaching mathematics. Thus, they develop the ability to think clearly about various mathematical judgments and conclusions, as well as develop problem-solving skills.